A triadic relationship on the northern Great Plains: bison (Bison bison), native plants, and native people - Garrett, James J., author; Woodmansee, Robert G., advisor (Colorado State University. Libraries, 2007)
The dissertation investigates and documents the historic relationship that exists among Bison bison, native plants, and Native People. An exhaustive in-depth review of each ecological component is given. Lakota Indian participants were interviewed for their qualitative knowledge of the three ecological components being studied. Interviewees were selected for their individual expertise in ethnobotany. Lokota culture, and/or indigenous ecological knowledge. Participant contributions are synthesized into a running narrative that describes the relationship in intimate detail. Detailed analysis shows that there are many facets to the relationship that exists among the three major ecological components. Recommendations are made for further research and the appendices include Lokota terminology, interview protocol and questions, data codes, and maps of Lakota territory before and after colonization.
Keywords: Bison bison; Great Plains; Lakota Indians; native plants; ecology; range management; Native American studies